Implementasi Aplikasi Kasir/Point Of Sales Berbasis Website Penjualan Alat Tulis Sekolah Wesley Pelita Bangsa - Maula Thoman Sihotang; Ramayanti, Desi (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2025)
This study aims to design and implement a web-based Point of Sales (POS) application as a solution to automate the stationery sales process at Wesley Pelita Bangsa School. The existing manual sales management causes inefficiencies and potential errors in stock recording and financial reporting. The development method used is the Waterfall model, which includes the stages of requirement analysis, system design, implementation, testing, and maintenance. Data were collected through observation, interviews, and literature review to ensure that both functional and non-functional system requirements were met. The implemented POS system successfully automates stock reduction during transactions, automatic receipt generation, and accurate, easily accessible sales reporting. System testing using Blackbox Testing demonstrated that the application operates according to specifications without significant errors. Therefore, this application can improve operational efficiency, reduce recording errors, and support the smooth learning process at Wesley Pelita Bangsa School. This research provides practical contributions to sales management and can serve as a reference for developing similar systems in non-formal educational environments.